A lectotype for Cyathophora richardi Michelin 1843 - Zaman, Shaahin; Lathuilière, Bernard (Zootaxa, 2014)
The figured syntype of Cyathophora richardi Michelin 1843, type species of the genus Cyathophora Michelin 1843, was recovered from the collection of the Muséum national d’Histoire naturelle (MNHN, Paris, France). It is herein designated as a lectotype in order to keep the traditional usage of the widely used genus Cyathophora.